Electroporation of Mesenchymal Stem Cells for the Secretion of Factor IX - Markar, Azra Z. (My University, 2012)
Mesenchymal stem cells have shown potential for success in gene therapy due to their ability to differentiate and their immunomodulatory properties in vivo. Although they have many inherent characteristics that are suitable for use within gene therapy, genetic modification of these cells is more difficult. Since MSCs are available in limited quantities and cannot be expanded indefinitely, the modification technique must ensure efficient expression of the transgene, a high cell survival rate and an intact ability to differentiate to various cell lineages. We optimized electroporation conditions for the genetic engineering of bone marrow-derived and umbilical cord blood-derived mesenchymal stem cells. MSCs engineered using electroporation conditions produced more transgene expression than cells engineered with cationic lipids in bone marrow-derived mesenchymal stem cells, but produced similar amounts in umbilical cord blood-derived mesenchymal stem cells. Optimal electroporation conditions also expressed more transgene than polymer based transfection reagent in umbilical cord blood-derived mesenchymal stem cells. Cell survival after optimal electroporation conditions was 67% in umbilical cord blood-derived mesenchymal stem cells. Most importantly, cells maintained their ability to differentiate into osteogenic, chondrogenic and adipogenic cell lineages. Electroporating umbilical cord blood-derived mesenchymal stem cells with a Factor IX containing plasmid lead to the FIX protein being expressed for over 12 days in vitro. This optimized electroporation protocol has created a fast, easy, economic and efficient method for genetically modifying mesenchymal stem cells without altering their ability to differentiate.
Keywords: Mesenchymal stem cell; electroporation; hemophilia; gene therapy; genetic engineering; cell therapy; stem cell; factor IX; Molecular, cellular, and tissue engineering; Molecular, cellular, and tissue engineering